THE STRENGTH OF NOTARIAL DEED MADE BY NOTARY EMPLOYEE ON BEHALF OF NOTARY SENTENCED TO MORE THAN 5 YEARS OF IMPRISONMENT - Fitri Abdillah Nur Ma’rifah; Noor Fatimah Mediawati (PT. Antis International Publisher, 2025)
Objective: This article discusses the strength of deeds made by notary employees on behalf of Notary after being sentenced to more than 5 years in prison. Method: This research uses normative juridical method with statute approach. Results: The result of the research is that Notary who is sentenced to imprisonment of 5 years or more will be dishonorably discharged by the Minister. Which means that the Notary no longer has the authority as a Notary. Therefore, the legal force of a deed made by a notary employee on behalf of a Notary who has been sentenced to imprisonment for more than 5 years and has lost his authority is considered invalid, has no legal force and is considered a deed forgery. If a notary employee acts outside of his/her authority, the authentic deed he/she produces will not be legally binding and cannot be executed. Parties harmed by such actions can file a civil lawsuit against the notary at the District Court. Novelty: This article highlights the legal consequences and invalidity of deeds made by notary employees on behalf of a Notary who has lost his authority due to imprisonment exceeding 5 years, emphasizing the legal boundaries of notary authority and accountability within Indonesian law.